2019
DOI: 10.3390/electronics9010024
|View full text |Cite
|
Sign up to set email alerts
|

Biometrics Using Electroencephalograms Stimulated by Personal Ultrasound and Multidimensional Nonlinear Features

Abstract: Biometrics such as fingerprints and iris scans has been used in authentication. However, conventional biometrics is vulnerable to identity theft, especially in user-management systems. As a new biometrics without this vulnerability, brain waves have been a focus. In this paper, brain waves (electroencephalograms (EEGs)) were measured from ten experiment subjects. Individual features were extracted from the log power spectra of the EEGs using principal component analysis, and verification was achieved using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Like already discussed in first part of the paper and confirmed by (3) and 11, the magnetic saturation, for a given excitation, restrains the usable frequency range at its lower margin. Thus, the experiments are focused to investigate if and how the proposed prefluxing circuit helps in overcoming this limitation.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…Like already discussed in first part of the paper and confirmed by (3) and 11, the magnetic saturation, for a given excitation, restrains the usable frequency range at its lower margin. Thus, the experiments are focused to investigate if and how the proposed prefluxing circuit helps in overcoming this limitation.…”
Section: Methodssupporting
confidence: 72%
“…Ultrasound-based techniques and systems are nowadays exploited in several very different areas. Biomedical investigations [1][2][3][4][5], non-destructive tests (NDT) [6][7][8], ultrasound levitation [9], nuclear safety [10], industrial monitoring of production processes [11][12][13], robotics [14], Doppler investigations [15], personal identification [16], and oil industry [17] are just a few examples of the employments that confirm the widespread presence of ultrasounds in our modern world. Although high-end systems, like clinical or research echograph [18][19][20], employ hundreds of independent ultrasound channels and require specific frond-end electronics [21,22], most of the aforementioned applications are based on a single ultrasound channel, and are preferably realized through discrete electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The person authentication method using evoked EEG via ultrasound stimuli is explained below. In previous studies [4], [5], it was confirmed that ultrasound stimuli generated unique EEG responses. In addition, it was also confirmed that the authentication performance was improved especially in the β wave band when ultrasound stimulus created using the favorite songs of the experimental participants (personal ultrasound) were used to elicit more individual differences in the evoked responses.…”
Section: Person Authentication Using Evoked Eeg By Ultrasoundmentioning
confidence: 61%
“…Iula and Micucci [13] have validated the use of biometrics relying on ultrasound images. Nakanishi and Maruoka [14] have proposed a biometric authentication using electroencephalograms stimulated by ultrasound. To obtain cancelable templates Wang et al [51] used transformation that is non-invertible on the binary fingerprint presentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The limitations of the traditional frameworks can be overcome by using biometrics, which is based on biometric traits of a human [12,13]. Biometric data of a human has gained immense popularity for user authentication and sensors are also easily available for presently [14]. Non-invasive biosensors are available for forensics, biometrics, and cybersecurity [15].…”
Section: Introductionmentioning
confidence: 99%